Nanomedicine Strategies for Anti‐Inflammatory Treatment of Noninfectious Arthritis. Issue 11 (18th April 2021) - Chen, Long; Wang, Yuanzheng; Sun, Li; Yan, Jerry; Mao, Hai‐Quan
Abstract: Noninfectious arthritis (NIA) comprises a class of chronic and progressive inflammatory disorders that require early‐stage management to prevent disease progression. The most common forms include osteoarthritis, rheumatoid arthritis, ankylosing spondylitis, and gouty arthritis. Current treatments involve nonsteroidal anti‐inflammatory drugs, disease‐modifying antirheumatic drugs and glucocorticoids to alleviate clinical symptoms, although regular use of these can result in a high risk of chronic kidney disease and heart failure, as well as severe adverse gastrointestinal effects. Nanomedicine offers unique opportunities to address these challenges and improve therapeutic efficacy due to its ability to deliver therapeutics locally in a sustained manner, thus extending the half‐life, improving bioavailability, and reducing the side effects of these agents. This review includes a comprehensive analysis of the mechanisms of various treatment options for NIA and highlights recent progress and emerging strategies in treating NIA with nanomedicine platforms, particularly related to long‐term biosafety and nonspecific targeting in designing nanomedicine delivery systems. Abstract : This review presents nanomedicine strategies for noninfectious arthritis, including systemic, intraarticular, and transdermal administration of drug delivery systems. Following a general introduction to mechanisms of various treatment options for noninfectious arthritis, the recent progress and emerging strategies are highlighted.